2018
DOI: 10.3389/fmicb.2018.00961
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Response to Organic Solvents and Possible Implications on Cross-Resistance With Antimicrobial Agents

Abstract: Mycobacterium vaccae, a bacterium found in soil, has been receiving attention as adjuvant to antituberculosis treatment, vaccines and immunotherapies and even as antidepressant. This bacterium is also able to degrade several pollutants, including aromatic compounds. The increasing presence of organic solvents in the environment may lead to M. vaccae adapted populations. A possible relationship between solvent tolerance and decreased susceptibility to other types of chemicals, including antibiotics, may pose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 94 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…To evaluate the effect of disinfectants commonly used in health care facilities on M. vaccae cells, the disinfectants were initially added at sub-lethal concentrations to cultures in mid-exponential phase. This classical approach, to study the effect of toxic compounds, allows de novo synthesis of fatty acids, if necessary, for the response of the cells at the membrane composition level [ 19 , 31 ]. After the addition of the disinfectant, the cells were monitored for 8 h. For comparison, the fatty acid (FA) composition of the exposed M. vaccae cells is presented after 6 h, which is higher than one duplication time in the presence of all tested disinfectants ( Figure 1 , Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the effect of disinfectants commonly used in health care facilities on M. vaccae cells, the disinfectants were initially added at sub-lethal concentrations to cultures in mid-exponential phase. This classical approach, to study the effect of toxic compounds, allows de novo synthesis of fatty acids, if necessary, for the response of the cells at the membrane composition level [ 19 , 31 ]. After the addition of the disinfectant, the cells were monitored for 8 h. For comparison, the fatty acid (FA) composition of the exposed M. vaccae cells is presented after 6 h, which is higher than one duplication time in the presence of all tested disinfectants ( Figure 1 , Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a model containing a lipid bilayer as outer membrane and an inner membrane, rich in diacyl phosphatidylinositol dimannosides, which also contribute to the generalized drug resistance of mycobacteria, has been proposed [ 48 ]. We have also shown that changes in the lipid composition of the cell envelop of M. vaccae contribute to the adaptation of this bacterium to organic solvents [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations